Comparative toxicological evaluation of nonylphenol and nonylphenol polyethoxylates using human keratinocytes. (2nd October 2018) - Kim, Hyungjoo; Oh, Sunhwa; Gye, Myung Chan; Shin, Incheol
Abstract: Nonylphenol polyethoxylates (NPEOs) are a major group of nonionic surfactants widely used in various detergents, cleaners, plastics, papers, and agro-chemical products. Nonylphenol (NP), which is a final degraded metabolite derived from NPEOs, has been reported as an endocrine disrupter, known to mimic or disturb reproductive hormone functions. Concern about the hazards of NP and NPEOs has generated legal restrictions and action plans worldwide. Considering the fact that NP and NPEOs are majorly used in the production of products such as detergents, shampoos, and cosmetics which frequently come into contact with the skin, we investigated the effects of NP and NPEOs on a human keratinocyte cell line (HaCaT). In this study, the toxicity of NP and NPEOs was screened in HaCaT cells using the 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide thiazolyl blue assay and Western blotting. The potential cytotoxicity of substitutes was assessed by dose-response assays, relative cell viability, and genotoxicity caused by specific alterations in DNA damage response proteins (including ataxia-telangiectasia mutated, p53, Chk1, Chk2, and Histone H2A.X). We demonstrated that NP and NPEOs are toxic to HaCaT cells, as revealed by the decreased cell viability after 24 h treatment. NPs and NPEOs also induced apoptosis and DNA damage as shown by the activation of Poly(ADP-ribose) polymerase, Caspase-3, and Histone H2A.X.